Mitochondrial DNA variation of Triatoma infestans populations and its implication on the specific status of T. melanosoma - Fernando A Monteiro; Ruben Pérez; Francisco Panzera; Jean-Pierre Dujardin; Cleber Galvão; Deyse Rocha; Francois Noireau; Chris Schofield; Charles B Beard (Memorias do Instituto Oswaldo Cruz, 1999)
DNA sequence comparison of 412 base-pairs fragments of the mitochondrial cytochrome B gene was used to infer the genetic structure of nine geographical Triatoma infestans populations and their phylogenetic relationship with T. melanosoma and T. brasiliensis. T. infestans and T. melanosoma were compared by morphometry, allozyme and cytogenetic analyses, as well as subjected to reciprocal crosses, in order to clarify the taxonomic status of the latter. No differences were found to distinguish the two species and the crosses between them yielded progeny. T. infestans populations presented four haplotypes that could be separated in two clusters: one formed by the samples from Bolivia (Andes and Chaco) and the other formed by samples from Argentina and Brazil. Silvatic and domestic T. infestans populations from Bolivia (Andes) were genetically identical.